Interdisziplinäre Dokumentations- und Visualisierungsmethoden - Trinkl, Elisabeth (Verlag der Österreichischen Akademie der Wissenschaften, 2013)
This publication focuses on (natural) scientific methods in studying and analyzing ancient pottery and discusses several case studies of the application on ancient vases stored in the Kunsthistorisches Museum Wien, Universalmuseum Joanneum Graz, and Collection of the Karl-Franzens-Universität Graz. So called non-invasive methods (without sampling) are favored, e. g. using high-resolution computer tomography, X-ray fluorescence analysis.